Renal transplant outcomes in patients with autosomal dominant tubulointerstitial kidney disease. Issue 2 (5th February 2020) - Cormican, Sarah; Kennedy, Claire; Connaughton, Dervla M.; O'Kelly, Patrick; Murray, Susan; Živná, Martina; Kmoch, Stanislav; Fennelly, Neil K.; Benson, Katherine A.; Conlon, Eoin T.; Cavalleri, Gianpiero L.; Foley, Claire; et al.
Abstract: Introduction: Autosomal dominant tubulointerstitial kidney disease (ADTKD) is a rare genetic cause of chronic kidney disease (CKD) and end‐stage renal disease (ESRD). We aimed to compare renal transplant outcomes in people with ESRD due to ADTKD to those with other causes of renal failure. Methods: Patients with clinical characteristics consistent with ADTKD by the criteria outlined in the 2015 KDIGO consensus were included. We compared ADTKD transplant outcomes with those of 4633 non‐ADTKD renal transplant recipients. Results: We included 31 patients who met diagnostic criteria for ADTKD in this analysis, 23 of whom had an identified mutation (28 were categorized as definite‐ADTKD and 3 as suspected ADTKD). Five patients received a second transplant during follow‐up. In total, 36 grafts were included. We did not identify significant differences between groups in terms of graft or patient survival after transplantation. Twenty‐five transplant biopsies were performed during follow‐up, and none of these showed signs of recurrent ADTKD post‐transplant. Conclusion: In patients with ESRD due to ADTKD, we demonstrate that transplant outcomes are comparable with the general transplant population. There is no evidence that ADTKD can recur after transplantation.